What shall we teach undergraduates?. Issue 6166 (24th March 1979) - Wright, V; Hopkins, R; Burton, K E
Abstract : The opinions of 600 randomly selected doctors on what should be taught to undergraduates in clinical years were analysed. The respondents gave a high priority to general medicine, paediatrics, general surgery, casualty, and gynaecology, but a low priority to forensic medicine, plastic surgery, radiotherapy, anaesthetics, radiology, and rehabilitation medicine. Doctors thought that these should be taught to postgraduates. The two major groupings of doctors--general practitioners and consultants--gave essentially the same priorities. Undergraduate curricula cannot include all major specialities, so the results of this analysis may provide a useful basis for selecting the most suitable subjects. Criteria for including other specialties might be the ability and enthusiasm of the teachers and well-thought-out and academically sound teaching programmes.